1989
DOI: 10.1007/bf01225012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sensitivity of sea urchin sperm bioassays to metals and pesticides

Abstract: A simple sperm/fertilization bioassay, primarily using sea urchin gametes, has been developed and used by a variety of laboratories. This assay was recently refined into a standard test and is now being used by the U.S. Environmental Protection Agency and others for toxicity testing in marine waters. One factor that has lagged behind the development of this assay is the comparison of its sensitivity to various common toxicants as compared to other bioassay systems and life stages of other marine organisms. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
3
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 20 publications
9
50
3
1
Order By: Relevance
“…The EC50 of 11 g/L Cu measured in this study is at the low end of the range (11-120 g/L Cu) of reported EC50s for other species of sea urchin larvae (Kobayashi, 1977(Kobayashi, , 1980(Kobayashi, , 1981(Kobayashi, , 1994Rumbold and Snedaker, 1997;Phillips et al, 2003). D. antillarum larvae were also very sensitive to Ag with an EC50 below the range (14-100 g/L) of EC50s reported for other urchins (Dinnel et al, 1982(Dinnel et al, , 1983(Dinnel et al, , 1989Warnau et al, 1996). Current U.S. EPA Ambient Water Quality Criteria (AWQC) for Cu and proposed AWQC for Ag in marine systems are 3.1 and 2.9 g/L, respectively (U.S. EPA, 1980EPA, , 2003.…”
Section: Discussioncontrasting
confidence: 45%
“…The EC50 of 11 g/L Cu measured in this study is at the low end of the range (11-120 g/L Cu) of reported EC50s for other species of sea urchin larvae (Kobayashi, 1977(Kobayashi, , 1980(Kobayashi, , 1981(Kobayashi, , 1994Rumbold and Snedaker, 1997;Phillips et al, 2003). D. antillarum larvae were also very sensitive to Ag with an EC50 below the range (14-100 g/L) of EC50s reported for other urchins (Dinnel et al, 1982(Dinnel et al, , 1983(Dinnel et al, , 1989Warnau et al, 1996). Current U.S. EPA Ambient Water Quality Criteria (AWQC) for Cu and proposed AWQC for Ag in marine systems are 3.1 and 2.9 g/L, respectively (U.S. EPA, 1980EPA, , 2003.…”
Section: Discussioncontrasting
confidence: 45%
“…For example, our results suggest that stresses could have more insidious and pervasive impacts than previously acknowledged. The gamete phase has long been recognised as the most sensitive to stress (Dinnel et al, 1989;Marshall, 2006). Our study suggests that exposure to a stress during fertilisation not only will affect the number of zygotes that are produced but also may alter the performance of those zygotes that are produced -a doubly negative effect of stress that could reverberate across the life history.…”
Section: Discussionmentioning
confidence: 91%
“…Antim:,totic/antilarval: We have chosen sea urchin eggs as objects for this part of the screening because: (1) This has become a standard technique in tl~e field (e.g., Dinnel et al, 1989); (ii) they are easy to obtain; and (iii) this test yields very diverse information about general bioactivities, such as sperm motility inhibition, fertilization inhibition, antimitotic activity, "mutagenic" activity (abnormal development) and ciliary motility inhibition. At least the last three of ti~ese probably affect many marine larvae at the moment of settlement.…”
Section: Secondary Metabolitesmentioning
confidence: 99%